Application Of Piezoelectric Energy Harvesting At Airports: Energy Sources, Materials And Design - Amalia, Direstu; Suryan, Viktor; Martadinata, M. Indra; Komalasari, Yeti; Almuzani, Almuzani; Alamsyah, Muhammad; Arinda, Nabila Hasna; Darsana, Made Putra (INTECOMS: Journal of Information Technology and Computer Science, 2024)
Airports have many areas with intensive activities that can be potential sources for Piezoelectric Energy Harvesting because airports are places that produce much mechanical energy that has not been realized. This mechanical energy comes from various sources, such as passenger and visitor traffic, vehicle movement, elevator and conveyor use, and aircraft activity on runways and taxiways. The research methodology used is a Literature Review. This article reviews the factors that affect PEH, namely energy sources, materials, and design, and it is a literature study article related to smart airport technology. This article aims to establish hypotheses of influence between variables as a reference for further research. This literature review article will produce: 1) Energy source affects Piezoelectric Energy Harvesting; 2) Materials affect Piezoelectric Energy Harvesting; and 3) Design affects Piezoelectric Energy Harvesting. This research will produce a deeper understanding of the potential mechanical energy utilized at airports and how energy harvesting technology can be applied to optimize these mechanical energy sources. Hopefully, this article will provide an overview of designing Piezoelectric Energy Harvesting suitable for airports.